PELATIHAN PENGGUNAAN MICROSOFT POWERPOINT SEBAGAI ALAT PRESENTASI DI SMA IBRAHIMY 2 SUKOREJO - Manda Nuria Suhailatin Najwa; Mamluatur Rizkiyatun Nafiah; Zaehol fatah (Jurnal Padamu Negeri, 2025)
The Microsoft PowerPoint training program is one form of skill development in the use of information technology within the educational environment. This activity aims to enhance students’ understanding and skills in utilizing Microsoft PowerPoint as an effective and engaging presentation tool. The training was conducted on June 3, 2025, at the Laboratory of the Faculty of Science and Technology, involving 30 female students from Class X2 of SMA Ibrahimy 2 Sukorejo. The materials presented included an introduction to PowerPoint, steps for creating presentation slides, and hands-on practice sessions. The results of the training indicated a significant improvement in students’ ability to create independent and creative presentation media. It is expected that the participants will be able to apply the acquired skills in teaching and learning activities as well as in other contexts requiring structured and visual information delivery.